Analysing The Elements Affecting Tourists’ Level of Satisfaction in Kabale District: A Case Study of Lake Bunyonyi. - Akamutuha, Mackline (Kabale University, 2024)
Satisfaction has been found as one of the elements that affect a tourist’s level of satisfaction. Several studies continue to indicate Scenic Beauty as the most significant factors that influence tourist satisfaction this positively increases the level of tourism development, but the extent to which these cases are associated with tourism development trends was not known. This study aimed to fill this research gap. A cross-sectional study in which a mixed method of inquiry was used to collect data using a questionnaire. The questionnaire had both open and closed-ended questions to capture both quantitative and qualitative responses. A sample of study participants was drawn from the elements affecting tourists’ level of satisfaction. A total sample of 133 participants was selected. Result: Of the 133 participants that were interviewed, 62.4% were male respondents and 37.6% were female respondents) considering the age of respondents, the highest number 47.4% belonged to the age group of 31-40years Conclusion: The study found that Scenic Beauty was 92% being the most factor that influenced tourist satisfaction this positively increases the level of tourism development in Kabale district: a case study of Lake Bunyonyi.The study proposed the following recommendations; Increase awareness of the level of satisfaction and importance of promoting tourists' satisfaction, Develop and implement intervention and sustainable tourism programs to address new satisfaction of tourists, Train employees on new technologies and the benefits in promoting and developing, Conduct further research to gain a better understanding of the complex relationship between tourists satisfaction development, development of tourism industry and the community involvement in the context of kabale municipality. .